Argentinian potato leafroll virus P0 protein : Novel activities for a previously known suppressor - Barrios Baron, Maria Pilar (2021)
The potato leafroll virus (PLRV) P0 protein (P0PL) is a suppressor of RNA silencing. In this study, we showed that P0 protein from an Argentinian isolate of PLRV (P0PL‐Ar) has an additional activity not described for other PLRV or P0 proteins from poleroviruses. Besides reporting that P0PL‐Ar displays both local and systemic silencing suppressor activity, we demonstrated, for the first time, that P0PL‐Ar impedes accumulation of dsRNA‐derived siRNAs. We also showed that P0PL‐Ar interacts with Solanum tuberosum SKP1 orthologue (StSKP1) and triggers destabilization of ARGONAUTE 1 (AGO1) and that these actions are mediated by the F‐box‐like domain. A mutant in the GW/WG motif within the P0PL‐Ar F‐box‐like motif lost the suppression activity, the interaction with StSKP1 and abolished AGO1 decay. Interestingly, a mutant in the L76/P77 residues within the P0PL‐Ar F‐box‐like motif, which lost the suppression activity and the interaction with StSKP1, retained the capacity to enable AGO1 decay. Thus, unlike other P0 proteins of previously characterized poleroviruses, P0PL‐Ar seems to have a dual activity, according to the findings of this study. This protein would act at both an upstream and a downstream step of the RNA silencing pathway: upstream of Dicer‐like enzyme (DCL)‐mediated primary siRNA production and downstream at the RNA‐induced silencing complex (RISC) complex level. Our results contribute to the understanding of the different ways PLRV P0 proteins function as silencing suppressors.